ANALISIS KESULITAN SISWA DALAM PEMAHAMAN KONSEP FUNGSI DAN FAKTOR PENYEBABNYA - Rini Agustini; Redi Hermanto; Dedi Muhtadi (Universitas Islam Nusantara, 2025)
This study aims to identify and analyze the types of difficulties students encounter in understanding the concept of functions, along with the contributing factors, based on indicators of conceptual understanding in mathematics. Using a qualitative descriptive approach, data were collected through diagnostic tests and semi-structured interviews with eighth-grade students at a junior high school in Tasikmalaya, Indonesia. The findings reveal that students face difficulties in six key areas: restating the definition of a function, distinguishing between examples and non-examples of functions, classifying objects based on the criteria of functions, applying concepts algorithmically, generalizing patterns from contextual situations into algebraic forms, and representing concepts graphically. These difficulties stem from weak cognitive structures, epistemological obstacles, limited meaningful learning experiences, and the dominance of procedural approaches in mathematics instruction. The results highlight the urgent need for instructional interventions that emphasize conceptual understanding, the connection among multiple representations, and the development of contextual and reflective learning designs based on students’ actual learning needs.